(untitled) (Research, Society and Development, 2021)
Acne severe/moderate is a self-limited genetic-hormonal disease that is related to the inflammatory process of the pilosebaceous apparatus, leading to the formation of abscesses (purulent nodules) and intercommunicating cysts, besides possible systemic alterations. The prognosis is variable; the sooner the correct treatment with oral isotretinoin is done, and the instructions of the dermatologist are followed, the better the outcome for the patient. Objective: To analyze whether there is a correlation between the use of oral Isotretinoin in patients with severe/moderate acne, and a negative impact on their mental health. Methodology: Case analysis that has the characteristic of being an observational study of prospective character and presents a qualitative approach. The information was obtained by means of questionnaires and data collection from the patients’ medical records, which could only be done after written authorization by signing the Informed Consent Form (ICF) and the consent of the Research Ethics Committee of the Patos University Center (UNIFIP). Results: The proposed study obtained a positive result regarding the effects of the medication in the treatment of severe/moderate acne, as well as on the mental health of the patients. Conclusion: Thus, it may contribute significantly to the better well being of patients in treatment, as well as to a better conduct on the part of professionals when it comes to greater care with the psychic effects related to the medication.